Skyline patellofemoral radiographs can only exclude late stage degenerative changes. - McDonnell, S; Bottomley, N; Hollinghurst, D; Rout, R; Thomas, G; Pandit, H; Ostlere, S; Murray, D; Beard, D; Price, A (2011)
Accurate preoperative assessment of the patellofemoral joint is especially important in compartment specific knee arthritis. This study aims to show the actual intraoperative grade of patellofemoral cartilage damage that may be reliably detected or excluded by preoperative standard radiographic views. 100 consecutive knees awaiting arthroplasty underwent preoperative lateral and skyline radiographs and were scored using the Ahlback score. Intraoperative cartilage damage was assessed using the Collins score. The sensitivity and specificity were calculated for each grade of cartilage damage. Preoperative anterior knee pain and function were assessed and correlated to the degree of cartilage damage. The lateral radiograph shows poor sensitivity for all grades of disease (0.05-0.23). The skyline shows good sensitivity for grade 4 (large full thickness) damage (0.90) but decreases substantially for grades 1-3 (0.19-0.46). Significantly more people with skyline radiograph joint space narrowing complained of anterior knee pain than those with a normal radiograph (p<0.001). There was only a poor correlation between preoperative anterior pain and intraoperative patellofemoral cartilage damage (r=0.24). The lateral radiograph cannot exclude even large areas of full thickness cartilage damage whereas a normal skyline radiograph can reliably exclude significant (grade 4) patellofemoral disease and should be used in addition to the lateral view.